Civil Society and Peacebuilding : Potential, Limitations and Critical Factors - World Bank (Washington, DC, 2012)
This report develops and discusses a new analytical framework to understand the functions of civil society in peace building. In theory and practice, there is a wide variety of ways to categorize civil society contributions to development and peacebuilding. Donors tend to employ actor-oriented perspectives, focusing on supporting activities of different types of civil society organizations in a given situation. This report proposes to move toward a functional perspective, centered on the roles that different actors can play in conflict situations. The analysis shows that civil society can make numerous positive contributions and have unique potential to support peacebuilding and conflict mitigation. It can do so independently as actor in its own right, or in relation to peacebuilding processes and programs led by Governments or the international community. Despite many successful initiatives on the ground, however, civil society should not be considered a panacea. The existence of civil society per se cannot be equated with the existence of peacebuilding actors. Similarly, civil society strengthening and support does not automatically contribute to peacebuilding. While civil society organizations are frequently actors for peace, they equally have the potential to become actors of violence. So far, outcomes and impacts of different civil society peace interventions have not been sufficiently evaluated. Civil society and donors need to more strategically identify the objectives and demonstrate the relevance of the particular approaches they propose to engage in different phases of conflict/peacebuilding. Without greater clarity regarding objectives and intended impacts, and, without addressing existing institutional constraints and distortions, activities run the risk of being well-intentioned, but unlikely to achieve sustainable results.